STRUCTURAL AND COMPOSITIONAL FEATURES OF DIALOGIC SPEECH IN THE ANECDOTE GENRE (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the linguistic, pragmatic, cognitive, and psycholinguistic features of humor within the framework of dialogic speech. Based on the modern linguistic tendency toward a comprehensive study of speech, the communicative function of humorous dialogic speech, its role in enhancing interactivity, and its significance in regulating social relations are examined. The study also analyzes the role of linguistic devices such as presupposition, implication, ellipsis, irony, and wordplay in creating implicit meaning in humorous dialogic texts. Furthermore, the stylistic expressiveness of dialogic humor, its affinity with colloquial forms, and its importance in expressing friendly relations between communicators are scientifically substantiated.
Keywords: dialogic speech, humor, anecdote (joke), linguistic pragmatics, interdiscursivity, presupposition